Investigating the level of Hba1c and insulin level in β-thalassemia patients - Mujiburrahman, Husnan; Santosa, Qodri; Setyono, Joko; Roestijawati, Nendyah; Rujito, Lantip (MEDISAINS, 2023)
Background: β-thalassemia is an inherited blood disorder characterized by reduced or no synthesis of β globin chain, resulting in chronic anemia, so blood transfusion is required as curative therapy. Repeated blood transfusions lead to iron overload that can lead to multiple organ damage, including pancreatic organs.Objective: This study aimed to describe HbA1c and insulin levels of β-thalassemia patients. The study also tested whether there was a significant difference in insulin and HbA1c levels among patients with different β-thalassemia categories. Method: This research was an analytic observational study. The samples were taken by total sampling and involved 30 patients, and the examination was carried out using the patient's blood plasma.Result: The study found that samples had low HbA1c levels. There was no significant mean difference (p>0.05) between insulin and HbA1c in the mild, moderate, and severe clinical degree groups. There was no significant difference in average (p>0.05) insulin and HbA1c in the thalassemia sufferers with allele β+ and β0 types.Conclusion: There was a decrease in insulin and HbA1c in patients with β-thalassemia, which may be caused by damage pancreatic organ damage.